FRAGMENTED GOVERNANCE AND INSTITUTIONAL LEGITIMACY IN POST-GADDAFI LIBYA: PATHWAYS TOWARD NATIONAL RECONCILIATION - Emmanuel Ifeakaonye NMOR; Johnson Okoroafor NDUBUISI; Patrick Ikechukwu CHUKE (Pinisi Journal of Social Science, 2025)
Since the overthrow of Muammar Gaddafi in 2011, Libya has experienced persistent political instability, institutional fragmentation, and violent conflicts, leading to a severe legitimacy crisis. The absence of a unified central authority has resulted in parallel governments, militia dominance, economic mismanagement, and foreign interference, further complicating national reconciliation efforts. This study examines the fragmented governance and institutional legitimacy crisis in post-Gaddafi Libya while exploring viable pathways toward national reconciliation. It adopts the historical research method, relying on secondary sources such as policy reports, scholarly works, and official documents. Through qualitative content analysis, the study critically evaluates political developments, institutional failures, and reconciliation efforts over time. It highlights key challenges, including the lack of inclusive political dialogue, a fragmented security sector, and uneven economic distribution, which have deepened divisions across the country. The study argues that national reconciliation is only achievable through inclusive political dialogue, security sector reform, economic stabilization, transitional justice, and reduced foreign influence. Establishing a transparent electoral roadmap, integrating militias into a unified national army, ensuring fair oil revenue distribution, and promoting grassroots-level peace-building initiatives are essential for rebuilding Libya’s institutional legitimacy. The study recommends a Libyan-led reconciliation process, supported by regional and international mediation efforts, with a strong focus on justice, security, and governance reforms. By addressing these structural issues, Libya can move toward long-term stability, national unity, and the restoration of public trust in state institutions..Kata kunci: (keyword) fragmented governance, institutional legitimacy, post-Gaddafi Libya, national reconciliation, political instability